PEMUTAKHIRAN PETA DASAR PENDAFTARAN TANAH KE DIGITAL TERKAIT SERTIFKAT GANDA DI INDONESIA - Joshea Frederick, (2022)
Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 12 of 2017 concerning Acceleration of Complete Systematic Land Registration has regulated land ownership and, however, land disputes still result in multiple certificates. The author uses a normative juridical research method and uses a legal study approach in the community with an approach to legislation and collects primary and secondary data for further analysis. This research focuses on updating the ix Basic Map of Land Registration which should be emphasized in the regulations in order to avoid overlapping problems and duplicate certificates in the example of Decision Number: 062/G/2014/PTUN.SMG. The conclusion that can be drawn from the results of this research is that the updating of the Basic Land Registration Map must be carried out and formed first, to support changes to the regulations established by the government in the issue of Dual Certificates.